Effectiveness of Implementing Clinical Practice Guidelines for prevention of hypothermia among patients undergoing cesarean section and under spinal anesthesia, Maharaj Nakorn Chiangmai Hospital - Jareonrattanadaechakul, Natatikarn; Sukhupragarn, Wariya (Biomedical Sciences and Clinical Medicine, 2024)
Objective To examine the effectiveness of implementing clinical practice guidelines (CPGs) for prevention of hypothermia among patients undergoing cesarean section and under spinal anesthesia, Maharaj Nakorn Chiang Mai hospital Methods The operational study was conducted. The sampling population included 26 patients in the non-CPGs group and 28 patients in the CPGs group. All patients were female who were undergoing cesarean section and under spinal anesthesia. The instrument was the CPGs for prevention of hypothermia. Primary outcome was the incidence of hypothermia and shivering. The secondary outcome was the patient’s comfortable temperature. The study based on a framework of implementing CPGs of the Australian National Health and Medical Research Council. Chi-square test and mean were used for the data analysis. Result The incidence rate of hypothermia in the CPGs group was lower than those in the non-CPGs group in all stages of the operation. In the preoperative period, hypothermia was decreased from 7.69% to 0% (p =0.227). Intraoperative period, the incidence of hypothermia decreased from 65.38% to 7.14% (p =0.000). Postoperative period, hypothermia decreased from 7.69% to 3.57% (p =0.604). The incidence of shivering was reduced in all stages of operation in the CPG-implementing group; 34.62% to 14.29% (p =0.081), and 11.54% to 7.14% (p =0.578), preoperative and postoperative period, respectively. Our result also presented that the patient’s comfortable temperature was increased in all stages of the operation (p =0.000). Discussion The controlling of factors infl uencing the implementing of CPGs was effective, such as room temperature operation, temperature fl uid, using a device to keep warm and a communication for information to a multidisciplinary team. Conclusion The results showed that the implementing of the CPGs for prevention of hypothermia was effective in patients undergoing cesarean section and under spinal anesthesia.